Sejarah dan Korelasi Filsafat Hukum Islam dengan Ilmu Lainnya - Andriyaldi, Andriyaldi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2015)
Compared ushul fiqh (islamic jurisprudence), studies maqashid sharia (Islamic legal philosophy) in the world of academics campus, relatively younger. Thus, studies and scientific discussions regarding maqashid sharia or Islamic law philosophy somewhat lagging. For the study and discussion on the need and importance increased and intensified. The discussion on the philosophy of Islamic law and syariah maqashid, just a lot of aspects mentioned in the history books of fiqh and usul fiqh issues by some jurists among Muslims. That is, at the level of a perfect concept study of philosophy of Islamic law rather neglected. Therefore, it can not be denied, Imam Shafi'i fiqh ushul more color and dominate the world ushul jurisprudence where more rests on the concept istinbathiy (rational deduction), while the study sharia maqashid more focused on the level of the concept istiqraiy (induction rational). Istiqraiy concept (rational induction) is precisely what is superior and comprehensive in view of a case when applying the laws of Islam, especially in the context of a complex modernity with contemporary issues. Broad perspective and thorough consideration readings and more owned by scholars who apply the concept of rational induction (istiqraiy). This concept, the precursor and seeds have been around since the revelation was dropped, because the true goal of Islamic law is as rahmatan li al-'alamin or maslahah in maqahid language sharia or Islamic legal philosophy. This paper describes the historical aspects of science maqashid sharia (Islamic legal philosophy) from the classical to the modern era.